KARAKTER BIOKIMIA TANAMAN KEDELAI YANG BERPERAN DALAM RESISTENSI TERHADAP LALAT BIBIT Ophiomyia phaseoli TRYON - Muliani, Yenny (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2013)
Soybean is a major botanical protein source and widely consumed by people in Indonesia. Development of soybean varieties has an important role in increasing local soybean production in order to reduce import from other countries. The spesific research target was to obtain resistant soybean varieties to beanfly, which supported the Indonesian Goverment’s Integrated Pest Management (IPM) Program. Experimental methods was applied in the field trial. Descriptive method in qualitative approach was applied in the analyzing the characteristics of the soybean varieties. Eight varieties of soybean were studied, i.e. Malika, Wilis, Kaba, Mitani, Mutiara, Bromo, Anjasmoro and Grobogan. Mutiara was the only resistant variety, Malika, Wilis, Kaba, and mitani, Bromo and Anjasmoro were moderately resistant,. Grobogan was highly susceptible. Low total N content, the high tannin content, and low water content determine the resistance to beanfly attack O. phaseoli.